Production and characterization of carbon/carbon composites from thermoplastic matrices - dos Santos Conejo, Luiza [UNESP]; de Meneses Neto, Hermes Rocha [UNESP]; de Oliveira, Juliana Bovi [UNESP]; de Paula Santos, Luis Felipe [UNESP]; Nakazato, Roberto Zenhei [UNESP]; de Oliveira Hein, Luis Rogerio [UNESP]; Kok, Winand; Botelho, Edson Cocchieri [UNESP] (Springer Nature, 2021)
Carbon-carbon composites (C/C) are those that have carbonaceous matrix reinforced with carbon fiber. They are widely used in the aerospace field, due mainly to the properties such as low density, high stiffness, and excellent thermal resistance, in comparison to the ones with polymer or metallic matrix. They are obtained through composites of polymer matrix (thermoset or thermoplastic), from the heat treatment of carbonization. The objective of this work is to produce the C/C composite material from three different thermoplastic laminates (PEKK/CF, PEEK/CF and LMPAEK/CF) as well as to compare these materials with C/C composites obtained from thermoset matrices, to show their advantages and disadvantages in relation to them. Such comparison was substantiated with TGA, DSC, SEM and XRD analyzes. In this work, the TGA showed the proposed process presents a lower mass loss, resulting in a faster and cheaper process, comparing thermoplastic with thermoset laminates. The DSC tests provided the basis for establishing the different heating rates. Through the SEM images it was possible to analyze the carbonization process. Finally, analyzes of cyclic voltammetry were made; through a comparison with Platinum electrode, C/C electrodes proved to be suitable for this application. Also, electrodes obtained from PEEK/CF presented better electrochemical responses.
Keywords: Carbon/carbon composites; Thermal analyses; Thermoplastic matrix